The Structure, Conduct, and Performance of the Midstream Segments of the Aquaculture Value Chain in Bangladesh - Ali, Hazrat; Belton, Ben; Khondker, Murshed-E-Jahan; Hernández, Ricardo; Haque, Mohammad Mahfujul (WorldFish, 2022)
The presentation talked about the comprehensive statistically representative study of 329 aquatic product traders in 31 markets from seven districts in south and southwest Bangladesh between January and May 2021to look into the organization and behavior of actors in these segments of the aquaculture value chain in Bangladesh.